Bakti Peran Teknologi Informasi dalam Proses Kegiatan Belajar Mengajar di Sekolah Dasar - Harlen Simanjuntak; Bakti toni Endaryono; Balyan (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to discuss and determine the Role of Information Technology in the Process of Teaching and Learning Activities in Vocational Secondary School, The method used in this research is descriptive qualitative research with substantive theory based on concepts arising from empirical data data obtained from secondary data and the corresponding literature with studies and according to field conditions. The results of this study are the role of information technology in teaching and learning activities (KBM) including: making it easier to deliver lessons, students can easily understand the lessons delivered by the teacher, and effective learning for teachers to achieve maximum learning process according to the rules of education and so forth.